The Implementation of Embodied Learning: A Literature Review - Sani, Yulvia; Wardany, Ossy Firstanti; Herlina, Heni; Vernanda, Genesa (Universitas Negeri Semarang, 2021)
This literature review aims to determine the implementation of the embodied learning approach in children. The research method used is a narrative review of ten articles that have met the criteria. The criteria for the article are to be found in Google Scholar, published in the last 8 years (2012-2021), and the title contains